False-Positive Positron-Emission Tomography-CT of a Teflon Granuloma in the Parapharyngeal Space Occurring after Treatment for a Patulous Eustachian Tube - Kirsch, C.F.E.; Suh, J.D.; Lufkin, R.B.; Canalis, R.F. (American Journal of Neuroradiology, 2007)
SUMMARY: This report presents a 55-year-old woman who underwent 2 Teflon injections in 1971 for a patulous eustachian tube. The patient returned in 2006 with a bloody left otorrhea. A positron-emission tomography-CT scan demonstrated a 2-cm hypermetabolic parapharyngeal mass, initially interpreted as a skull base tumor. Repeat neck CT confirmed a 2-cm hyperattenuated left parapharyngeal granulomatous mass. This is the first reported case of a Teflon granuloma presenting as a false-positive parapharyngeal mass.